2009
DOI: 10.1007/s11064-009-0089-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-Acetylcysteine/Deferoxamine, Taurine and RC-3095 on Respiratory Chain Complexes and Creatine Kinase Activities in Rat Brain After Sepsis

Abstract: The pathogenesis of sepsis is characterized by an overwhelming systemic inflammatory response that can lead to multiple organ failure. Considering that we have recently demonstrated that mitochondrial respiratory chain and creatine kinase (CK) are altered in the brain of rats after cecal ligation and perforation (CLP) and that a combination of N-acetylcysteine/deferoxamine (NAC/DFX), taurine and RC-3095 were shown to be an effective treatment of sepsis, we investigated whether the alterations of these enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 60 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Taurine is not involved in peptide bond formation, but it has various biological functions, such as bile acid conjugation, maintenance of calcium homeostasis, osmoregulation, and membrane stabilization . In addition, antioxidant activity is another widely recognized function of taurine . Though taurine is a very stable molecule and difficult to oxidize, the sulfur‐containing acid still has an indirect antioxidant function, either by decreasing the reactive oxygen species (ROS) generation or by improving the antioxidant defense system …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taurine is not involved in peptide bond formation, but it has various biological functions, such as bile acid conjugation, maintenance of calcium homeostasis, osmoregulation, and membrane stabilization . In addition, antioxidant activity is another widely recognized function of taurine . Though taurine is a very stable molecule and difficult to oxidize, the sulfur‐containing acid still has an indirect antioxidant function, either by decreasing the reactive oxygen species (ROS) generation or by improving the antioxidant defense system …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] In addition, antioxidant activity is another widely recognized function of taurine. 11,12 Though taurine is a very stable molecule and difficult to oxidize, the sulfur-containing acid still has an indirect antioxidant function, either by decreasing the reactive oxygen species (ROS) generation or by improving the antioxidant defense system. 13,14 It has been reported that taurine can alleviate oxidative impairment caused by hydrogen peroxide via activating the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway and enhancing the heme oxygenase 1 (HMOX1) expression.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Specific agents like N-acetyl cysteine (NAC), NAME (N-nitro-L-arginine methyl ester), and desferrioxamine have been tried in some recent experimental studies. [3,4] NAC is a thiol compound with potent antioxidant and anti-inflammatory properties. It is also a well-known glutathione (GSH) precursor.…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant activity is one of the most important biological functions of taurine (Cassol et al, 2010;Das et al, 2012). Previous research suggested that the interaction of taurine with the plasma membrane results in a modulation of the membrane lipid ratio, thereby leading to a decrease in membrane fluidity and increased resistance to oxidative damage (Hamaguchi et al, 1991).…”
Section: Discussionmentioning
confidence: 99%